Quantum Molecular Resonance Inhibits NLRP3 Inflammasome/Nitrosative Stress and Promotes M1 to M2 Macrophage Polarization: Potential Therapeutic Effect in Osteoarthritis Model In Vitro - Teresa Paolucci; Vanessa Pino; Osama Elsallabi; Marialucia Gallorini; Gianantonio Pozzato; Alessandro Pozzato; Paola Lanuti; Victor Machado Reis; Mirko Pesce; Andrea Pantalone; Roberto Buda; Antonia Patruno (MDPI AG, 2023)
This study aimed to investigate the anti-inflammatory effects of Quantum Molecular Resonance (QMR) technology in an in vitro model of osteoarthritis-related inflammation. The study used THP-1-derived macrophages stimulated with lipopolysaccharide and hyaluronic acid fragments to induce the expression of inflammatory cytokines and nitrosative stress. QMR treatment inhibited COX-2 and iNOS protein expression and activity and reduced NF-κB activity. Furthermore, QMR treatment led to a significant reduction in peroxynitrite levels, reactive nitrogen species that can form during inflammatory conditions, and restored tyrosine nitration values to those similar to sham-exposed control cells. We also investigated the effect of QMR treatment on inflammasome activation and macrophage polarization in THP-1-derived macrophages. Results showed that QMR treatment significantly decreased NLRP3 and activated caspase-1 protein expression levels and downregulated IL-18 and IL-1β protein expression and secretion. Finally, our findings indicate that QMR treatment induces a switch in macrophage polarization from the M1 phenotype to the M2 phenotype.